Preparation method of green adhesive with biomimetic mineralization structure
By constructing a bionic mineralized structure in bio-based adhesives, using polysaccharide templates to induce the growth of CaCO3 biominerals, and combining soy protein and plant polyphenols, the problems of low bond strength and insufficient functionality of bio-based adhesives are solved, and a green adhesive with strong adhesion, versatility and environmental protection are achieved.
Patent Information
- Application Number
- CN202510119982.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-25
- Publication Date
- 2025-04-25
AI Technical Summary
The existing bio-based adhesives have low bond strength and insufficient functionality. Modification strategies usually damage toughness, increase process complexity and increase production costs. At the same time, due to low reactivity, enhancing functionality requires the addition of petroleum-based compounds, which damages environmental advantages.
By adsorbing calcium ions and carbonate ions layer by layer, the crystal nucleation and growth of CaCO3 biominerals is induced by combining soy proteins and plant polyphenols to establish a compatible interface and construct a green adhesive with a bionic mineralized structure.
Green adhesive with strong adhesion and versatility is achieved, with environmental protection and process adjustability, significantly improving adhesive strength and waterproofing, and excellent flame retardant and mildew-proof properties.
Smart Images

Figure CN119875579A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wood adhesives, and specifically relates to a method for preparing a green adhesive with a bionic mineralized structure. Background Art
[0002] The growing demand for adhesives in key industries such as aerospace, automotive, and construction is driving the global adhesives market to grow at a CAGR of 5% and is expected to reach $68.94 billion by 2024. Currently, adhesives made from fossil raw materials dominate the global market. However, the widespread use of these adhesives has raised concerns about greenhouse gas emissions, energy shortages, and risks to human health, highlighting the urgent need for green and sustainable alternatives.
[0003] Natural bio-based adhesives show great promise as alternatives to fossil-based adhesives because of their green, renewable and abundant sources. Common bio-based adhesives include plant proteins, lignin and polysaccharides. However, these bio-based adhesives often exhibit some limitations, including low bonding strength and insufficient functionality. On the one hand, their bonding strength depends largely on weak hydrogen bonds and physical entanglements, which are easily broken. Current modification strategies—such as chemical cross-linking, multi-network structures and nanomaterial doping—can improve bonding strength, but these methods usually compromise toughness, increase process complexity and increase production costs. On the other hand, due to the low reactivity of bio-based materials, enhancing the functionality of bio-based adhesives (such as flame retardancy, water resistance and mildew resistance) usually requires the addition of large amounts of petroleum-based compounds, which compromises the environmental advantages of bio-based adhesives and increases their ecological footprint. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a biomimetic mineralized structure green adhesive. The green adhesive prepared by the present invention has strong adhesion and multifunctionality, and is green and environmentally friendly.
[0005] The technical solution of the present invention is: a method for preparing a green adhesive with a biomimetic mineralization structure, which comprises dissolving polysaccharide in deionized water, adding calcium salt and stirring, then adding carbonate into the mixture, inducing crystal nucleation of CaCO3 biomineral by adsorbing calcium ions and carbonate ions layer by layer with polysaccharide as an organic template, collecting the product by vacuum filtration after the growth reaction to obtain CaCO3 biomineral; finally, mixing soybean protein with deionized water, then adding CaCO3 biomineral for ultrasonic treatment, and then adding plant polyphenols to establish a compatible interface between CaCO3 biomineral and soybean protein, thereby obtaining a green adhesive with a biomimetic mineralization structure.
[0006] In the aforementioned method for preparing the biomimetic mineralized structure green adhesive, the polysaccharide includes chitosan, sodium alginate and starch.
[0007] In the aforementioned method for preparing the biomimetic mineralized structure green adhesive, the calcium salt includes calcium chloride, calcium acetate and calcium oxalate; the carbonate includes sodium carbonate, potassium carbonate and sodium bicarbonate.
[0008] In the aforementioned method for preparing the biomimetic mineralized structure green adhesive, the plant polyphenols include ellagic acid, tannic acid and gallic acid.
[0009] In the preparation method of the aforementioned biomimetic mineralized structure green adhesive, the preparation of the CaCO3 biomineral is to dissolve 0.3-2.4 parts of polysaccharide in deionized water by mass, stir for 20-30 minutes at 50-60°C, then add 17.4-121.5 parts of calcium salt and stir for 50-60 minutes, add 16.8-117 parts of carbonate to the mixture and stir for 7-8 hours, and vacuum filter to obtain the CaCO3 biomineral.
[0010] In the above-mentioned preparation method of biomimetic mineralized structure green adhesive, the mass part of the polysaccharide is 0.9 parts, the temperature is 55°C, and the stirring time is 20 minutes; the mass part of the calcium salt is 52.2 parts, and the stirring time is 60 minutes; the mass part of the carbonate is 50.1 parts, and the stirring time is 8 hours.
[0011] In the preparation method of the aforementioned bionic mineralized structure green adhesive, 8-15 parts of soy protein and 85-92 parts of deionized water are mechanically stirred at 25-35°C at a speed of 300-400rpm for 10-15min, and then 1-7 parts of CaCO3 biominerals are added and placed in an ultrasonic cleaner for ultrasonic treatment for 10-20min, and then stirred at 25-35°C for 50-60min, and then 4-10 parts of plant polyphenols with a polyphenol hydroxyl structure are added, and stirred at 20-40°C for 30-40min to obtain a green adhesive product.
[0012] In the preparation method of the above-mentioned biomimetic mineralized structure green adhesive, the mass part of the soy protein is 12 parts, the mass part of the deionized water is 88 parts, the temperature of the mechanical stirring is 25°C, the speed of the mechanical stirring is 350rpm, and the mechanical stirring time is 10min; the mass part of the CaCO3 biomineral is 3 parts, the time of the ultrasonic treatment is 15min, the temperature of the stirring after the ultrasonic treatment is 25°C, and the time of the stirring after the ultrasonic treatment is 60min.
[0013] In the aforementioned method for preparing the biomimetic mineralized structure green adhesive, the process of establishing a compatible interface is to add 4-10 parts of plant polyphenols having a polyphenolic hydroxyl structure and continue stirring at 20-40° C. for 30-40 minutes.
[0014] In the above-mentioned method for preparing the biomimetic mineralized structure green adhesive, the mass parts of the plant polyphenols are 6 parts, the stirring temperature is 35° C., and the stirring time is 35 min.
[0015] Compared with the prior art, the green adhesive of the present invention uses a simple and effective strategy to construct a biomimetic mineralized structure to develop a strong and multifunctional soybean protein adhesive, and uses polysaccharides as organic templates. The CaCO3 biomineral obtained by the biomimetic mineralized structure is environmentally friendly and process adjustable, and is more environmentally friendly; the present invention also introduces an economical and efficient natural polyphenol to establish a compatible interface between the CaCO3 biomineral and soybean protein, so that the bonding strength is significantly improved, thereby obtaining a green adhesive with a biomimetic mineralized structure. In the adhesive system, the present invention significantly improves the bonding strength and waterproof ability of the soybean protein adhesive by using high-modulus CaCO3 biominerals and their ion chelation. In addition, the biomimetic mineralized structure of the present invention forms a continuous thermal barrier network, which makes it have excellent flame retardancy, and the synergistic effect of plant polyphenols and inorganic mineral components gives the soybean protein adhesive excellent mildew resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 This is a microscopic morphology of CaCO3 biomineral observed by electron microscope (TEM) of the present invention;
[0017] Figure 2 The particle size and particle size distribution diagram of the CaCO3 biomineral biomimetic mineralization structure of the present invention;
[0018] Figure 3 This is a mildew proof test diagram of the adhesive of the present invention. DETAILED DESCRIPTION
[0019] The present invention is further described below in conjunction with the accompanying drawings and embodiments, but they are not intended to limit the present invention.
[0020] Example 1: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0021] Step 1: Dissolve 0.09 g of chitosan in 289.68 g of deionized water, stir at 55°C for 20 min, then add 5.22 g of calcium acetate and stir for 1 h to obtain a mixture; then add 50.1 g of potassium carbonate to the mixture and stir for 8 h, and finally obtain CaCO3 biomineral by vacuum filtration;
[0022] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 350 rpm for 10 min at 25 ° C, and then 3 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 25 ° C for 60 min;
[0023] Step 3: Add 6 g of ellagic acid to the mixture prepared in step 2, stir at 35° C. for 35 min, and obtain a green adhesive product.
[0024] Example 2: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0025] Step 1: 0.09 g of starch was dissolved in 289.68 g of deionized water, stirred at 55°C for 20 min, and then 5.22 g of calcium oxalate was added and stirred for 1 h to obtain a mixture; then 50.1 g of sodium bicarbonate was added to the mixture and stirred for 8 h, and finally CaCO3 biomineral was obtained by vacuum filtration;
[0026] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 350 rpm for 10 min at 25 ° C, and then 3 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 25 ° C for 60 min;
[0027] Step 3: Add 6 g of gallic acid to the mixture prepared in step 2, stir at 35° C. for 35 min, and obtain a green adhesive product.
[0028] Example 3: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0029] Step 1: Dissolve 0.09 g of chitosan in 289.68 g of deionized water, stir at 55°C for 20 min, then add 5.22 g of calcium oxalate and stir for 1 h to obtain a mixture; then add 50.1 g of sodium carbonate to the mixture and stir for 8 h, and finally obtain CaCO3 biomineral by vacuum filtration;
[0030] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 350 rpm for 10 min at 25 ° C, and then 3 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 25 ° C for 60 min;
[0031] Step 3: Add 6 g of gallic acid to the mixture prepared in step 2, stir at 35° C. for 35 min, and obtain a green adhesive product.
[0032] Example 4: A method for preparing a biomimetic mineralized structure green adhesive is carried out according to the following steps:
[0033] Step 1: 0.03 g of sodium alginate was dissolved in 296.55 g of deionized water, stirred at 50° C. for 20 min, and then 1.74 g of calcium chloride was added and stirred for 1 h to obtain a mixture; then 1.68 g of sodium carbonate was added to the mixture and stirred for 8 h, and finally CaCO3 biomineral was obtained by vacuum filtration;
[0034] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 300 rpm for 10 min at 25 ° C, and then 1 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 10 min, and then mechanically stirred at 25 ° C for 70 min;
[0035] Step 3: Add 4 g of tannic acid to the mixture prepared in step 2, stir at 30° C. for 30 min, and obtain a green adhesive product.
[0036] Example 5: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0037] Step 1: Dissolve 0.09 g of sodium alginate in 289.68 g of deionized water, stir at 55°C for 20 min, then add 5.22 g of calcium chloride and stir for 1 h to obtain a mixture; then add 5.01 g of sodium carbonate to the mixture and stir for 8 h. Finally, obtain the CaCO3 biomineral by vacuum filtration;
[0038] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 350 rpm for 10 min at 25 ° C, and then 3 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 25 ° C for 60 min;
[0039] Step 3: Add 6 g of tannic acid to the mixture prepared in step 2, stir at 35° C. for 35 min, and obtain a green adhesive product.
[0040] Example 6: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0041] Step 1: Dissolve 0.18 g of sodium alginate in 282.78 g of deionized water, stir at 50°C for 25 min, then add 8.70 g of calcium chloride and stir for 50 min to obtain a mixture; then add 8.34 g of sodium carbonate to the mixture and stir for 8 h. Finally, obtain the CaCO3 biomineral by vacuum filtration;
[0042] Step 2: 11 g of soy protein and 89 g of deionized water were mechanically stirred at 350 rpm for 15 min at 30 ° C, and then 5 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 30 ° C for 60 min;
[0043] Step 3: Add 8 g of tannic acid to the mixture prepared in step 2, stir at 30° C. for 35 min, and obtain a green adhesive product.
[0044] Example 7: A method for preparing a biomimetic mineralized structure green adhesive, according to the following steps:
[0045] Step 1: Dissolve 0.24 g of sodium alginate in 275.91 g of deionized water, stir at 60°C for 20 min, then add 12.15 g of calcium chloride and stir for 1 h to obtain a mixture, then add 11.70 g of sodium carbonate to the mixture and stir for 7 h. Finally, obtain the CaCO3 biomineral by vacuum filtration;
[0046] Step 2: 12 g of soy protein and 88 g of deionized water were mechanically stirred at 400 rpm for 10 min at 35 ° C, and then 7 g of CaCO3 biomineral was added and ultrasonically treated in an ultrasonic cleaner for 15 min, and then mechanically stirred at 35 ° C for 60 min;
[0047] Step 3: Add 10 g of tannic acid to the mixture prepared in step 2, stir at 30° C. for 30 min, and obtain a green adhesive product.
[0048] Comparative Example: Each group was weighed according to the weight ratio, 12 g of soybean protein was added to 88 g of deionized water, and mechanical stirring was performed at a speed of 300 rpm for 10 min to obtain a conventional soybean protein adhesive.
[0049] Furthermore, the CaCO3 biomineral obtained in Example 5 was observed by electron microscope (TEM), and the following Figure 1 The microscopic morphology of the CaCO3 biomineral shown in FIG. 1 shows that the synthesized CaCO3 biomineral exhibits a typical calcite crystal morphology through TEM, showing a dense internal structure and a few and thin external stacking layers, which is consistent with the close stacking principle of ion crystal balls, and intuitively confirms the formation of the biomimetic mineralization structure of the CaCO3 biomineral. The CaCO3 biomineral obtained by the biomimetic mineralization structure of the present invention has adjustable particle size. The present invention changes the ratio of the prepared CaCO3 biomineral to affect the number of adsorbed ions, thereby regulating the particle size. The adjustable particle size and particle size distribution are shown in FIG. Figure 2 shown.
[0050] Furthermore, three-layer plywood was prepared using the adhesives of Examples 1-7 of the present invention and the comparative example respectively.
[0051] The plywood is made of poplar veneer: the moisture content is dried to 10%; the size is 20cm×20cm×0.15cm. The normal preparation process is as follows:
[0052] Gluing: The glue coating amount on the upper and lower surfaces of the core layer is 200g / m 2 ;
[0053] Pressure, temperature, time: 1Mpa, 120℃, 6min.
[0054] According to the Chinese national standard (GB / T 17657-2013), indoor plywood samples were tested for performance. The test results are shown in Table 1.
[0055] Table 1 Performance test of indoor plywood samples
[0056]
[0057] The cone calorimetry test was performed on the plywood samples according to the international standard (ISO5660-1:2015). The test results are shown in Table 2.
[0058] Table 2 Cone calorimetry test of plywood samples
[0059]
[0060] Since the adhesion of the comparative example is mainly provided by intermolecular hydrogen bonding, but hydrogen bonding is easily destroyed by water, the water-resistant bonding performance of the adhesive is poor (≤0.7MPa). After the introduction of CaCO3 biominerals and plant polyphenols, the wet shear strength of the adhesive is significantly improved, all greater than 0.7MPa, meeting the indoor use standards in "GB / T 9846-2015 Ordinary Plywood". This improvement is mainly due to the mineral reinforcement and ion chelation of CaCO3 biominerals, and the added plant polyphenols construct a compatible interface between soy protein and CaCO3 biominerals. The wet shear strength of the plywood made in Example 5 reached 1.20MPa, which is 185% higher than that of the comparative adhesive. This is because the catechol groups in the plant polyphenols form CaCO3 biominerals with CaCO3 biominerals. 2+-polyphenol coordination bonds, and form strong hydrogen bonds with the amino, carboxyl and hydroxyl groups of soybean protein. Plant polyphenols act as "molecular bridges" to improve the interfacial compatibility between the adhesive matrix and the CaCO3 biomineral, thereby improving the water resistance of the biomimetic mineralized adhesive. However, with the further increase of plant polyphenols and CaCO3 biomineral content, the dry and wet shear strengths of the adhesive both show a downward trend. This is because the plant polyphenol content is too high, forming a large number of hydrogen bonds, increasing the viscosity of the adhesive, and reducing the adhesive properties of the adhesive. However, the wet shear strength of Examples 1-7 is always maintained at more than 0.70MPa, showing stable and good adhesive strength, meeting the requirements for indoor use. It can be seen that the plywood wet shear strength obtained by the preferred process parameters in Example 5 is the highest, and its water resistance is the best.
[0061] Furthermore, the mildew resistance test of the adhesives of Examples 4-7 and the comparative example was performed. Figure 3 It is the result of the mildew resistance test. The comparative adhesive began to degrade and emit an unpleasant odor after 24 hours, and white mold hyphae appeared after 72 hours. Example 4-7 turned dark brown after 24 hours, but no mold growth was observed, and even after 144 hours, no mold was detected. The enhanced mildew resistance is due to the ability of tannic acid to inhibit mold growth and reproduction by changing the fungal structure and destroying the cell wall of the fungus. In addition, CaCO3 biominerals have inherent antibacterial properties. Therefore, the green adhesive with biomimetic mineralized structure exhibits excellent mildew resistance.
[0062] In summary, the green adhesive of the present invention constructs a biomimetic mineralization structure through a simple and effective strategy to develop a strong and multifunctional soybean protein adhesive, and uses polysaccharides as organic templates. The CaCO3 biomineral obtained by the biomimetic mineralization structure has environmental protection and process adjustability, and is more green and environmentally friendly; the present invention also introduces an economical and efficient natural polyphenol to establish a compatible interface between the CaCO3 biomineral and soybean protein, so that the bonding strength has been significantly improved, thereby obtaining a green adhesive with a biomimetic mineralization structure. In the adhesive system, the present invention significantly improves the bonding strength and waterproof ability of the soybean protein adhesive by using high modulus CaCO3 biominerals and their ion chelation. In addition, the biomimetic mineralization structure of the present invention forms a continuous thermal barrier network, which makes it have excellent flame retardancy, and the synergistic effect of plant polyphenols and inorganic mineral components gives the soybean protein adhesive excellent mildew resistance. The green adhesive prepared by the present invention has strong adhesion and multifunctionality, and is green and environmentally friendly.
Claims
1. A method for preparing a biomimetic mineralized structure green adhesive, characterized in that: The polysaccharide is dissolved in deionized water, and then calcium salt is added and stirred. Then carbonate is added to the mixture. The polysaccharide is used as an organic template to adsorb calcium ions and carbonate ions layer by layer to induce crystal nucleation of CaCO3 biomineral. After the growth reaction is completed, the product is collected by vacuum filtration to obtain CaCO3 biomineral. Finally, soy protein is mixed with deionized water, and then CaCO3 biomineral is added for ultrasonic treatment. Plant polyphenols are then added to establish a compatible interface between the CaCO3 biomineral and the soy protein, thereby obtaining a green adhesive with a biomimetic mineralization structure.
2. The method for preparing the biomimetic mineralized structure green adhesive according to claim 1, characterized in that: The polysaccharides include chitosan, sodium alginate and starch.
3. The method for preparing the biomimetic mineralized structure green adhesive according to claim 1, characterized in that: The calcium salts include calcium chloride, calcium acetate and calcium oxalate; the carbonates include sodium carbonate, potassium carbonate and sodium bicarbonate.
4. The method for preparing the biomimetic mineralized structure green adhesive according to claim 1, characterized in that: The plant polyphenols include ellagic acid, tannic acid and gallic acid.
5. The method for preparing the biomimetic mineralized structure green adhesive according to claim 1, characterized in that: The preparation of the CaCO3 biomineral is as follows: 0.3-2.4 parts of polysaccharide are dissolved in deionized water by mass, stirred at 50-60°C for 20-30 minutes, then 17.4-121.5 parts of calcium salt are added and stirred for 50-60 minutes, 16.8-117 parts of carbonate are added to the mixture and stirred for 7-8 hours, and the CaCO3 biomineral is obtained by vacuum filtration.
6. The method for preparing the biomimetic mineralized structure green adhesive according to claim 5, characterized in that: The mass fraction of the polysaccharide is 0.9 parts, the stirring temperature of the polysaccharide dissolved in deionized water is 55° C., and the stirring time of the polysaccharide dissolved in deionized water is 20 minutes; the mass fraction of the calcium salt is 52.2 parts, and the stirring time is 60 minutes; the mass fraction of the carbonate is 50.1 parts, and the stirring time is 8 hours.
7. The method for preparing the biomimetic mineralized structure green adhesive according to claim 1, characterized in that: 8-15 parts of soybean protein and 85-92 parts of deionized water are mechanically stirred at 300-400 rpm for 10-15 minutes at 25-35° C., 1-7 parts of CaCO3 biominerals are added, and the mixture is ultrasonically treated in an ultrasonic cleaner for 10-20 minutes. The mixture is then stirred at 25-35° C. for 50-60 minutes. 4-10 parts of plant polyphenols having a polyphenol hydroxyl structure are then added, and the mixture is stirred at 20-40° C. for 30-40 minutes to obtain a green adhesive product.
8. The method for preparing the biomimetic mineralized structure green adhesive according to claim 7, characterized in that: The mass portion of the soy protein is 12 parts, the mass portion of the deionized water is 88 parts, the temperature of the mechanical stirring is 25°C, the speed of the mechanical stirring is 350rpm, and the mechanical stirring time is 10min; the mass portion of the CaCO3 biomineral is 3 parts, the time of the ultrasonic treatment is 15min, the temperature of stirring after the ultrasonic treatment is 25°C, and the time of stirring after the ultrasonic treatment is 60min.
9. The method for preparing the biomimetic mineralized structure green adhesive according to claim 7 or 8, characterized in that: The process of establishing the compatible interface is to add 4-10 parts of plant polyphenols having a polyphenolic hydroxyl structure and continue stirring at 20-40° C. for 30-40 minutes.
10. The method for preparing the biomimetic mineralized structure green adhesive according to claim 9, characterized in that: The mass parts of the plant polyphenols are 6 parts, the stirring temperature is 35° C., and the stirring time is 35 min.
Citation Information
Cited By
Cigarette filter stick based on biomimetic mineralization and preparation method thereof
CN121312878A
Environment-friendly soy protein phenol-formaldehyde resin adhesive and preparation method thereof
CN122686278A